2008
DOI: 10.1085/jgp.200709934
|View full text |Cite
|
Sign up to set email alerts
|

Gap Junction Channels Exhibit Connexin-specific Permeability to Cyclic Nucleotides

Abstract: Gap junction channels exhibit connexin dependent biophysical properties, including selective intercellular passage of larger solutes, such as second messengers and siRNA. Here, we report the determination of cyclic nucleotide (cAMP) permeability through gap junction channels composed of Cx43, Cx40, or Cx26 using simultaneous measurements of junctional conductance and intercellular transfer of cAMP. For cAMP detection the recipient cells were transfected with a reporter gene, the cyclic nucleotide-modulated cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 57 publications
5
81
0
Order By: Relevance
“…[37][38][39] These messengers regulate the adhesion and transendothelial diapedesis of leukocytes during inflammatory reactions. 40,41 In particular, ATP derivates might be important because it has recently been shown that Treg cells augment adenosine levels in vivo and in vitro, leading to suppression of effector T-cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] These messengers regulate the adhesion and transendothelial diapedesis of leukocytes during inflammatory reactions. 40,41 In particular, ATP derivates might be important because it has recently been shown that Treg cells augment adenosine levels in vivo and in vitro, leading to suppression of effector T-cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of [cAMP] levels in the effluent from buffer-perfused rabbit and rat vascular beds have shown that ACh and the SERCA inhibitor cyclopiazonic acid both stimulate prostanoid-independent efflux of cAMP from the endothelium [97,182]. Collectively, these observations suggest that smooth muscle cAMP levels might in part reflect diffusion of endothelium-derived cAMP into the arterial media via myoendothelial gap junctions containing Cx43 or Cx40 [99]. Candidate pathways leading to activation of endothelial adenylyl cyclase include (1) the formation of eicosanoids from arachidonic acid (see below) and (2) activation of specific Ca 2+ -stimulated isoforms of adenylyl cyclase (e.g., type 8) by store-operated Ca 2+ entry which can reflect the co-localization of this isoenzyme with store-operated Ca 2+ channels in membrane caveolae [194].…”
Section: Intrinsic Modulation Of the Edhf Phenomenonmentioning
confidence: 97%
“…2D). Different homotypic channels have distinct electrical and biochemical properties (7,40,49). In addition, heterotypic channels composed of different Cxs display different selectivity and permeability of second messengers such as IP 3 and cyclic nucleotides (79).…”
Section: Gap Junction Channelsmentioning
confidence: 99%